A two-step purification platform for efficient removal of Fab-related impurities: A case study for Ranibizumab - PİNAR, ORKUN; SARIYAR AKBULUT, BERNA; KAZAN, DİLEK (My University, 2023)
Antibodies (mAbs) and antibody fragments (Fabs) constitute one of the largest and most rapidly expanding groups of protein pharmaceuticals. In particular, antibody fragments have certain advantages over mAbs in some therapeutic settings. However, due to their greater chemical diversity, they are more challenging to purify for large-scale production using a standard purification platform. Besides, the removal of Fab-related byproducts poses a difficult purification challenge. Alternative Fab purification platforms could expedite their commercialization and reduce the cost and time invested. Accordingly, we employed a strong cation exchanger using a pH-based, highly linear gradient elution mode following Protein L affinity purification and developed a robust two-step purification platform for an antibody fragment. The optimized pH gradient elution conditions were determined on the basis of purity level, yield, and the abundance of Fab-related impurities, particularly free light chain. The purified Fab molecule Ranibizumab possessed a high degree of similarity to its originator Lucentis. The developed purification platform highly intensified the process and provided successful clearance of formulated Fab- and process-related impurities (∼98 %) with an overall process recovery of 50 % and, thus, might be a new option for Fab purification for both academic and industrial purposes.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Antibody fragment; Biosimilar production; Liquid chromatography; Mass spectrometry; Pharmaceutical purification